2022
DOI: 10.3390/foods11233783
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Aging Effect of Agrocybe aegerita Polysaccharide through Regulation of Oxidative Stress and Gut Microbiota

Abstract: Polysaccharides extracted from Agrocybe aegerita (AAPS) have various physiological effects. In this study, we used the naturally aging Drosophila melanogaster and D-galactose-induced aging mice as animal models to study the anti-aging effects of AAPS via the alleviation of oxidative stress and regulation of gut microbiota. Results showed that AAPS could significantly prolong lifespan and alleviate oxidative stress induced by H2O2 of Drosophila melanogaster. In addition, AAPS significantly increased the activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…41 The Firmicutes/ Bacteroidota ratio was significantly downregulated in the Dgalactose-induced senescence model, which is one of the hallmarks of senescence affecting the gut microbiota. 42 Our study also found that LPS treatment downregulated the ratio of Firmicutes/Bacteroidota, and puerarin treatment could restore the ratio of Firmicutes/Bacteroidota. Studies have shown that Lactobacillaceae could delay aging by changing the composition of the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 The Firmicutes/ Bacteroidota ratio was significantly downregulated in the Dgalactose-induced senescence model, which is one of the hallmarks of senescence affecting the gut microbiota. 42 Our study also found that LPS treatment downregulated the ratio of Firmicutes/Bacteroidota, and puerarin treatment could restore the ratio of Firmicutes/Bacteroidota. Studies have shown that Lactobacillaceae could delay aging by changing the composition of the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…This also provides a theoretical basis for the possibility that puerarin may delay mammary gland aging through the “gut-mammary axis.” Studies have shown that the ratio of Firmicutes and Bacteroidota changes with life stages . The Firmicutes/Bacteroidota ratio was significantly downregulated in the D-galactose-induced senescence model, which is one of the hallmarks of senescence affecting the gut microbiota . Our study also found that LPS treatment downregulated the ratio of Firmicutes/Bacteroidota , and puerarin treatment could restore the ratio of Firmicutes/Bacteroidota .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that dietary consumption of polysaccharides can retarded the aging process and alleviate age-related diseases by modulating gut microbiota. For example, polysaccharides extracted from Agrocybe aegerita (AAPSs) reshaped the disordered intestinal flora, increased the abundance ratio of Firmicutes to Bacteroidetes, increased the abundance of beneficial bacteria Lactobacillus , and exhibited a potential antiaging effect in d -galactose-induced aging mice …”
Section: Antiaging Effects Of Polysaccharidesmentioning
confidence: 99%
“…For instance, polysaccharides isolated from both the fruiting bodies and primordia of G. lucidum demonstrated neuroprotective properties [21,54,59,67]. In addition, based on the study conducted by Liu et al [68], it is known that polysaccharides from C. aegerita significantly prolong the lifespan of Drosophila melanogaster as a model organism and alleviate the oxidative stress induced by H 2 O 2 . Interestingly, G. applanatum, which exhibited significant AChE inhibition, also demonstrated a higher concentration of PUT and SPD compared to G. resinaceum.…”
Section: Ache Inhibitory Potentialmentioning
confidence: 99%